2023
DOI: 10.3389/fphys.2023.1215835
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of phosphodiesterases and adenylyl cyclase signaling pathway on red blood cell deformability of sickle cell patients

Evrim Goksel,
Elif Ugurel,
Elie Nader
et al.

Abstract: Sickle cell disease (SCD) is an inherited hemoglobinopathy characterized by chronic anemia, intravascular hemolysis, and the occurrence of vaso-occlusive crises due to the mechanical obstruction of the microcirculation by poorly deformable red blood cells (RBCs). RBC deformability is a key factor in the pathogenesis of SCD, and is affected by various factors. In this study, we investigated the effects of adenylyl cyclase (AC) signaling pathway modulation and different phosphodiesterase (PDE) modulatory molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Over 80 proteins were found to have supporting experimental evidence for their presence and activity in RBCs, yet they were not detected across all proteomic studies. For example, at least six different phosphodiesterase proteins have been identified in RBCs with important roles in regulating cyclic nucleotide levels [95], yet none were found in the proteomic data. Proteins involved in the synthesis of blood group antigens also do not appear across proteomic studies [96,97].…”
Section: Metabolomics and Literature Curation Verify Enzymatic Activi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over 80 proteins were found to have supporting experimental evidence for their presence and activity in RBCs, yet they were not detected across all proteomic studies. For example, at least six different phosphodiesterase proteins have been identified in RBCs with important roles in regulating cyclic nucleotide levels [95], yet none were found in the proteomic data. Proteins involved in the synthesis of blood group antigens also do not appear across proteomic studies [96,97].…”
Section: Metabolomics and Literature Curation Verify Enzymatic Activi...mentioning
confidence: 99%
“…signaling [95], degradation [128], and export [126]. Though early studies were unable to detect adenylosuccinate synthetase activity in RBCs [129], deep proteomic and metabolic tracing studies have demonstrated its presence and a residual activity [130].…”
mentioning
confidence: 99%
“…For example, mitophagy agents in SCD mouse models reduced mitochondrial retention in RBCs and increased RBC lifespan, suggesting a promising therapeutic approach ( Jagadeeswaran et al, 2017 ). Similarly, RBC channel blockers and cAMP-pathway modulators were explored in SCD to counteract cell dehydration and deformability issues, respectively ( Ataga et al, 2008 ; Goskel et al, 2023 ; Toppet et al, 2000 ). The new knowledge that RBCs perform low levels of protein synthesis could also be therapeutically useful; thus, drugs enabling stop codon readthrough might be useful for patients with beta-thalassemia who have premature stop codons in their beta-globin gene ( Kar et al, 2020 ; Kumar et al, 2022 ).…”
Section: A Dynamic Perspective On Rbc Biomarker and Drug Targeting Po...mentioning
confidence: 99%